(untitled) (Al-Qamar, 2022)
The study was conducted to address and explore the security dimension of Islamophobia in Hollywood movies. Therefore, the objective of the study is to investigate the representation of Muslims in Hollywood movies and to explore the securitization of Muslims. Securitization theory has been used as the theoretical framework of this study. The methodology used for this purpose consisted of quantitative analysis and analyzing three movies released by Hollywood. It was found that the portrayal of Muslims on Hollywood platforms is problematic and has produced securitized images of Muslims. Researchers selected three movies: American Sniper, The Dictator and Clean Skin, released by Hollywood movies by utilizing purposive sampling technique. The finding shows that The Dictator produced more securitized scenes than American Sniper and Clean Skin. All three movies produced nagative content related to Muslims. The Dictator and American Sniper produced more securitized images of Muslims Women as a Threat theme, Muslims as a Threat and Muslims Children as a Threat as compared to the Clean Skin. All of the three movies had produced very few scenes in the Immigrants and Refugees category. All three movies produced negative content on attributes related to Muslims category like, Turban. Cap, beard, Hijab and dress. Hollywood movies in the process of securitization of Muslims; Muslims are being linked with terrorism and extremism, and framed as a security threat. Hence, by following Islamophobic discourses, Hollywood movies have produced securitized the image of Muslims.